2000
DOI: 10.1046/j.1525-1497.2000.15200-19.x
|View full text |Cite
|
Sign up to set email alerts
|

In Search of a Good Death: Attitudes of Patients, Family Members and Health Care Professionals

Abstract: PURPOSE: Psychiatric disorders and abnormal personality traits are commonly identified in patients complaining of fatigue, most of whom can be diagnosed to have depressive (D), anxiety (A), somatoform (S) or eating (E) disorders. This study was designed to determine the relationship between the prevalence of severe fatigue and the presence of personality pathology in individuals with these psychiatric disorders. METHODS: We analyzed 1197 referrals to an academic psychosomatic medicine outpatient unit. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although accommodating the spiritual and cultural needs and values of patients and their loved ones is not a new intervention, this particular concept was only briefly mentioned in the nursing research literature, usually in the context of a form of ancillary support personnel for nurses in dealing with families as they cope with the death of their loved one. 6,13,18,23,27 Steinhauser et al 34 found that issues of faith were often mentioned as integral to EOL care and frequently became more important as the patient declined physically.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Although accommodating the spiritual and cultural needs and values of patients and their loved ones is not a new intervention, this particular concept was only briefly mentioned in the nursing research literature, usually in the context of a form of ancillary support personnel for nurses in dealing with families as they cope with the death of their loved one. 6,13,18,23,27 Steinhauser et al 34 found that issues of faith were often mentioned as integral to EOL care and frequently became more important as the patient declined physically.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Researchers contend that patients with chronic and debilitating illnesses are prompted to examine existential and spiritual issues as a means of adjusting to their illness and coping with the omnipresence of death [ 27 , 28 , 29 ]. Breitbart [ 30 ] delves further and suggests that end-of-life (EOL) “ symptoms relating to psychological distress and existential concerns are even more prevalent than pain and other physical symptoms.…”
Section: Background To Spirituality In Chronic Kidney Diseasementioning
confidence: 99%